(untitled) (African Journal of Law and Politics, 2023)
The right to self-determination is intrinsically tied to indigenous peoples’ rights over lands and natural resources, as a prerequisite to freely determine their political status and freely pursue their economic, social and cultural development; and their continuous recognition, protection and existence as distinct peoples. Thereon, guaranteeing the material and spiritual survival of indigenous peoples, whose economic, cultural and political organisations are intimately bound up with the territory that they have inhabited and the natural resources they have used since time immemorial, are all about guaranteeing them appropriate measures for their wellbeing and survival as ‘a peoples’ either from circumstances that directly threaten their community life, like the lack of access to food, access to property, medicinal plants or those conditions relevant for a minimum level of dignity such as their cultural and spiritual values. This paper adopts a socio-legal analytical research method, which questions how effective can the subsistence rights of indigenous peoples be justiciable under the ever-growing contentious human rights system of indigenous peoples. Although, there are no protection mechanisms under the specific human rights system of indigenous peoples, the jurisprudence of the African and the Inter-American human rights systems, have broken even, in providing remedies for the continuous survival of indigenous peoples.